RANCANG BANGUN DAN MONITORING PENYEARAH DAN ATS (AUTO TRANSFER SWITCH) PADA SISTEM MONITORING SUMBER DC GARDU INDUK BERBASIS ARDUINO MEGA 2560 - Wirawan, Herdoyo; Subari, Arkhan (Gema Teknologi, 2017)
Herdoyo Wirawan, Arkhan Subari, in this paper explain that the DC source at a PLN substation has a very important role in the smooth operation of the substation itself in a protection and serving the electricity needs of customers. This DC source serves to drive protective equipment, emergency lighting, and others.When the DC source on the receptor is interrupted, the dc source used is a DC source that comes from the battery. When certain conditions cannot guarantee whether the battery capacity is capable of supporting the load borne by the battery, it must always be monitored with a voltage sensor. In order for the protective equipment to continue to work, when the rectifier from the PLN power supply is cut off, a voltage source from 12VDC batteries is used. Switching the voltage source between the rectifier and the battery is done automatically by using the ATS (Automatic Transfer Switch) circuit. When the DC source from the PLN electricity supply will return it will be detected by an optocoupler sensor which later ATS will automatically switch the voltage source again.